2010
DOI: 10.1063/1.3520322
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Laser Wakefield Accelerators in a Lorentz Boosted Frame

Abstract: Modeling of laser-plasma wakefield accelerators in an optimal frame of reference [1] is shown to produce orders of magnitude speed-up of calculations from first principles. Obtaining these speedups requires mitigation of a highfrequency instability that otherwise limits effectiveness in addition to solutions for handling data input and output in a relativistically boosted frame of reference. The observed high-frequency instability is mitigated using methods including an electromagnetic solver with tunable coef… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 37 publications
(81 reference statements)
1
16
0
Order By: Relevance
“…Extensive testing confirmed, as was discussed elsewhere [25,34], that choosing the frame of the wake as the frame of reference allows for higher levels of filtering and damping than is possible in other frames with the same accuracy. It also revealed that there exists a singular time step for which the level of instability is minimal, independently of other numerical parameters, especially the numerical dispersion of the solver.…”
Section: Resultssupporting
confidence: 54%
See 4 more Smart Citations
“…Extensive testing confirmed, as was discussed elsewhere [25,34], that choosing the frame of the wake as the frame of reference allows for higher levels of filtering and damping than is possible in other frames with the same accuracy. It also revealed that there exists a singular time step for which the level of instability is minimal, independently of other numerical parameters, especially the numerical dispersion of the solver.…”
Section: Resultssupporting
confidence: 54%
“…Comparing the timings with those of Fig. 13 (middle-left) from [25] shows that the smoothing and the damping added less than a factor of two of total runtime to the simulations. These results lead to several observations:…”
Section: Scaled 10 Gev Stagesmentioning
confidence: 89%
See 3 more Smart Citations